The equation is 36 - 4x = 6.
Solution:
To write the equation without fraction.
![$4-(4)/(9) x=(2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/pp4ezbz9xltg31qexcenb735ogllarize4.png)
![$(4)/(1) -(4)/(9) x=(2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/dfwixfzh5qz9k56e82f6g17rnsc43ot9cx.png)
The denominators must be same to add/subtract the fractions.
LCM of 1, 9 and 3 = 9.
Multiply first term by
and
by
to make the denominator same.
![$(4*9)/(1*9) -(4)/(9) x=(2*3)/(3*3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3yh5bsnlgvvkvcb4h4u7x9ew6x7dmkdf1z.png)
![$(36)/(9) -(4)/(9) x=(6)/(9)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/31r76q1yk3jz4bfut5ek43dt04ere6cjov.png)
![$(36-4x)/(9) =(6)/(9)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/of2xb9r8iyg812sfbcj7g9zffssozsqmov.png)
Multiply by 9 on both sides.
![$(36-4x)/(9)*9 =(6)/(9)*9](https://img.qammunity.org/2021/formulas/mathematics/middle-school/4hhkjzpaijt7w2c4gcx6u7glefqzhrxulv.png)
Both 9 in the numerator and denominator get canceled.
36 - 4x = 6
This term does not have fraction.
Hence the equation is 36 - 4x = 6.